Neglected tropical diseases (NTDs) and vector control - Wondji, Charles (Henry Stewart Talks, 2019)
What are the NTDs and their vectors, Geographical distribution, Current approaches for prevention, Insecticides used for vector control, Current approaches for prevention, How can vector control play its full role: global vector control responses strategy